The Frankenstein’s Legacy: Transcranial Direct Current Stimulation in Promoting Speech and Language Recovery in Post- Stroke Dysphasia: Malaysian’s Experience - N , Mohamad Hashim; NFF , Jamil; NF , Ahmad Roslan; WN, Mohd Zohdi; M, SF Salim; SN, Kamarudin (IIUM Medical Journal Malaysia, 2020)
Transcranial Direct Current Stimulation (tDCS) is an adjunct to behavioral speech therapy to enhance the recovery of post-stroke dysphasia. Administration of tDCS involves the application of low- amplitude electrical currents through surface electrodes, which are placed onto the scalp to influence the neuronal activity.TDCS montage and patients’ clinical characteristics are the important factors in determining the outcome of the intervention. We aim to describe the clinical characteristics, outcomes and local limitation factors of five post-stroke patients who received TDCS combined with behavioural therapy for dysphasia. All patients, except for Case #5 showed improvement at day 10 post-intervention in several speech and language domains. TDCS is a promising adjunctive intervention in enhancing neuroplasticity activity in a post-stroke brain. A further well design case-controlled study is warranted to prove its efficacy in our local population. Local factors and limitations that may influence the outcome should be considered.